Così Fan Tutte: Why a right to be forgotten should not be pursued - Martha Garcia-Murillo; Ian MacInnes (International Telecommunications Society (ITS), 2014)
In W.A. Mozart's opera Così Fan Tutte the protagonists are put through a social experiment to move from a state of innocence to one of experience. The goal is to understand that the idealized characterization of a perfect mate is unrealistic. We must accept the weaknesses of others as well as the setbacks that occur in the real world even though the lessons can be bitter. In this article we use secondary research and logical argumentation to show that the dissemination of personal information through public and private databases as well as social media is gradually educating humanity of the enlightened lessons that Mozart and his librettist Lorenzo da Ponte identified: humans are weak; everyone misbehaves; and we should accept public knowledge of the imperfections of ourselves and others. In the presence of so much information about people, how can society best protect us from potential harm? As we learn more about others through self-disclosed or other means we are noticing that while some people make egregious mistakes, most of us are moving toward a more realistic expectation of human behavior. We thus argue that the European Union directive on 'the right to be forgotten' is misguided and unrealistic and suggest instead a series of principles that can protect us from the potentially harmful publication of private information.
Keywords: 330